2018
DOI: 10.3390/antibiotics7010009
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Regression Model to Study Host-Genomic Determinants of Phage Susceptibility in MRSA

Abstract: Staphylococcus aureus is a major agent of nosocomial infections. Especially in methicillin-resistant strains, conventional treatment options are limited and expensive, which has fueled a growing interest in phage therapy approaches. We have tested the susceptibility of 207 clinical S. aureus strains to 12 (nine monovalent) different therapeutic phage preparations and subsequently employed linear regression models to estimate the influence of individual host gene families on resistance to phages. Specifically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…More phage resistance systems likely remain undiscovered. A genome-wide association study of 207 clinical MRSA strains and 12 phage preparations identified 167 gene families putatively associated with phage-bacterium interactions (131). While these families included restriction-modification genes, transcriptional regulators, and genes of prophage and SaPI origin, most were accessory gene families of unknown function.…”
Section: Other Phage Host Range-limiting Factorsmentioning
confidence: 99%
“…More phage resistance systems likely remain undiscovered. A genome-wide association study of 207 clinical MRSA strains and 12 phage preparations identified 167 gene families putatively associated with phage-bacterium interactions (131). While these families included restriction-modification genes, transcriptional regulators, and genes of prophage and SaPI origin, most were accessory gene families of unknown function.…”
Section: Other Phage Host Range-limiting Factorsmentioning
confidence: 99%
“…In addition, although many S. aureus phages are reported to have wide host ranges (28)(29)(30)(31)(32)(33)(34), and even early studies suggested staphylococcal phage therapies to be highly effective (35), experiments conducted thus far have failed to explain the genetic bases of host range or resistance development in a species-wide manner. Only one previous study has associated genetic factors (gene families) with phage resistance using a hypothesis-free method (36). This work used a two-step linear regression model to associate some 167 gene families, mostly of unknown function, with resistance assessed in 207 clinical MRSA strains and 12 phage preparations.…”
Section: S Aureus Phages and Corresponding Known Host Mechanisms Regmentioning
confidence: 99%
“…Differential phage susceptibility determinants that are encoded by various strains of the same species include genes encoding phage receptors or pathways of their synthesis and phage-compatible restriction-modification systems [ 149 , 150 , 151 , 152 , 153 , 154 , 155 ]. Additionally, bacteria encode phage defence mechanisms, but these mechanisms protect the bacterium by itself either from infection with certain phages or from phage propagation, or induce apoptosis to protect the population from spread of the infection [ 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 ]. The differential phage susceptibility determinants are exchangeable between strains of a given species.…”
Section: Future Possibilities To Produce Industrial Phage Propagamentioning
confidence: 99%